2020
DOI: 10.1016/j.patrec.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Opinion fraud detection via neural autoencoder decision forest

Abstract: Online reviews play an important role in influencing buyers' daily purchase decisions. However, fake and meaningless reviews, which cannot reflect users' genuine purchase experience and opinions, widely exist on the Web and pose great challenges for users to make right choices. Therefore, it is desirable to build a fair model that evaluates the quality of products by distinguishing spamming reviews. We present an end-to-end trainable unified model to leverage the appealing properties from Autoencoder and rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Therefore, it is desirable to build a fraud detection model to identify and weed out fake reviews. Dong et al (2018) [145] present an autoencoder and random forest, where a stochastic decision tree model fine tunes the parameters. Extensive experiments were conducted on a large Amazon review dataset.…”
Section: A Fraud Detection In Financial Servicesmentioning
confidence: 99%
“…Therefore, it is desirable to build a fraud detection model to identify and weed out fake reviews. Dong et al (2018) [145] present an autoencoder and random forest, where a stochastic decision tree model fine tunes the parameters. Extensive experiments were conducted on a large Amazon review dataset.…”
Section: A Fraud Detection In Financial Servicesmentioning
confidence: 99%
“…Kontschieder et al [24] introduced a stochastic, differentiable, backpropagation compatible version of decision forest, guiding representation learning in the lower layers of deep convolutional networks. Based on this, Dong et al [25] combined an autoencoder with it into a joint model to detect opinion fraud. In this work, Dong et al first employed statistical analysis to define a list of quality measures for online reviews and then used the autoencoder to generate the hidden representations of these features.…”
Section: Related Workmentioning
confidence: 99%
“…Supervised learning techniques that have been used for spam review detection so far are; Rule based classification [5,10], Unified model [2], Logistic Regression [4,11,12], Knearest neighbor (KNN) [4], Random Forest [4,[13][14][15], Decision Trees [16,17], Gradient Decent [4,10], Genetic Algorithm [18], Conceptual Model [19], Time Series [20], Neural Network [21], Deep Neural Network [22], Multinomial Naïve Bayes [9,11,13], N-Gram [13], Hybrid Learning Approach (Active and supervised learning) [23], RNN, CNN [24], and Multilayer Perceptron Model (MLP) [4,24], Unsupervised learning is a category of machine learning that work on the unlabeled datasets. Many unsupervised learning techniques have been used in spam detection which are: Natural Language Processing [6,9][58] Markov Network [25], Neural Auto-encoder Decision Forest [16]¸ and PU Learning [26]. Other than these supervised and unsupervised learning techniques, there are many other techniques that have been used for spam detection such as Fuzzy Logic [27], Heterogeneous Information Network [28], Hadoop [29], Text Mining [30], Sentiment Analysis [31][32][33][34]<...>…”
Section: Figure 1 Types Of Spammentioning
confidence: 99%
“…However, Jindal and Liu identified that many spam reviews were written in a way that it looks authentic. Hence, they determined that using duplication feature to differentiate legitimate reviews and spam reviews is not suited for creating label datasets [16].…”
Section: Figure 1 Types Of Spammentioning
confidence: 99%